2015
DOI: 10.5406/amerjpsyc.128.2.0229
|View full text |Cite
|
Sign up to set email alerts
|

Can Multiple-Choice Testing Induce Desirable Difficulties? Evidence from the Laboratory and the Classroom

Abstract: The term desirable difficulties (Bjork, 1994) refers to conditions of learning that, though often appearing to cause difficulties for the learner and to slow down the process of acquisition, actually improve long- term retention and transfer. one known desirable difficulty is testing (as compared with restudy), although typically it is tests that clearly involve retrieval—such as free and cued recall tests—that are thought to induce these learning benefits and not multiplechoice tests. nonetheless, multiple- c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…Furthermore, follow‐up studies showed that it was the mental effort per se involved in the retrieval of the information during the intervention (intermediate test) that accounted for much of the gains (Endres and Renkl ). Bjork and others () agree and highlight the need for a certain level of “desirable difficulty” for the intermediate testing to result in increased recall (Bjork and others ). Therefore, it is reasonable to hypothesize that benefits of the testing may be obtained from any activity requiring high mental effort.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Furthermore, follow‐up studies showed that it was the mental effort per se involved in the retrieval of the information during the intervention (intermediate test) that accounted for much of the gains (Endres and Renkl ). Bjork and others () agree and highlight the need for a certain level of “desirable difficulty” for the intermediate testing to result in increased recall (Bjork and others ). Therefore, it is reasonable to hypothesize that benefits of the testing may be obtained from any activity requiring high mental effort.…”
Section: Discussionmentioning
confidence: 90%
“…Exams and quizzes are stress‐ and anxiety‐inducing activities (Nguyen and McDaniel ) and references therein), and benefits of test‐enhanced learning maybe gender‐biased (Kromann and others ). Furthermore, poorly constructed multiple‐choice pre‐exams with implausible alternative answers do not result in meaningful learning gains (Bjork and others ). Frequent quizzes may also be seen by students as an attempt to assert (or even usurp) authority by the instructor, and thus undermine development of the student‐centered participatory classroom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5] General education concepts show that practice tests can contribute to improved performance on standardized tests via comprehension calibration, study plan development, and application of metacognitive strategy. [6][7][8][9][10][11][12][13] fmCASES are online case-based modules originally created to meet the Society of Teachers of Family Medicine's National Clerkship Curriculum Objectives, 14 and were found to "foster self-directed and independent study" and "emphasize and model clinical problem-solving." 15 During the time of this initiative, 146 medical schools in the United States utilized fmCASES to teach or assess student learners.…”
mentioning
confidence: 99%